Biological Flora of the British Isles: Crambe maritima. (28th March 2015) - Sanyal, Anushree; Decocq, Guillaume
Summary This account presents information on all aspects of the biology of Crambe maritima L. (Sea‐kale; Crambe pontica Stev. ex Rupr) that are relevant to understand its ecological characteristics and behaviour. The main topics are presented within the standard framework of the Biological Flora of the British Isles: distribution, habitat, communities, responses to biotic factors, responses to environment, structure and physiology, phenology, floral and seed characters, herbivores and disease, history and conservation. Crambe maritima is found predominantly on southern and western coasts of Britain but also in Scotland, Ireland and elsewhere. It occurs primarily on neutral or slightly alkaline soils on shingle and sand beaches above the drift line, out of reach of average high tides. Equinoctial tides or storms can increase soil salinity, requiring it to be salt tolerant. Crambe maritima is a rosette plant with a fleshy taproot, which is the main perennating organ with a capacity for vegetative propagation. Flowering can take 5–8 years when grown from seeds. Reproduction is predominantly by seeds. Root and stem cuttings can be used for vegetative propagation. In winter, each branch ends at ground level in a leafless crimson bud, and in spring, it produces a succession of cabbage‐like leaves just above ground level, the first being purple and successive leaves becoming greener. Crambe maritima produces weakly protogynous hermaphrodite flowers. Self‐ and cross‐pollination occurs. Pollination is by insects, flies and bees. The plants usually produce 1000–10 000 seeds per year. In Britain, Crambe maritima has been reported to have declined in certain areas but increased in other areas and currently does not have rare or scarce status. There has been an expansion in range in Ireland since the 1960s as it has been recorded at new sites, and while the species has disappeared from some sites in France, it has also been identified in several new sites.